2010
DOI: 10.1002/cyto.b.20552
|View full text |Cite
|
Sign up to set email alerts
|

Early and rapid detection of X-linked lymphoproliferative syndrome with SH2D1A mutations by flow cytometry

Abstract: Background: X-linked lymphoproliferative syndrome (XLP) is a rare immunodeficiency with extreme vulnerability to Epstein-Barr virus (EBV) infection. It presents with fatal infectious mononucleosisResults: The method demonstrated that SAP was intensely expressed in CD8 1 T cells and NK cells in normal fresh blood samples, thus suggesting the possible rapid identification of individuals with SAP deficiency. SH2D1A mutations were identified in six patients with SAP deficiency, but not in patients with normal SAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
1
16
0
3
Order By: Relevance
“…Consistent with these previous reports, we observed that memory (CD45RO + ) CD8 T cells from donors 3 and 4 that display the conventional unimodal pattern of SAP expression with the 1C9-SAP Ab clone also expressed higher levels of SAP in terms of median fluorescence intensity (MFI) (2.5-4 times greater than the [CD45RO 2 ] CD8 T cells) (Supplemental Fig. 2) (29). This trend was repeated when we gated on their IFNg-producing CD8 T cells as the IFN-g + CD45RO + CD8 T cells displayed a higher MFI for SAP compared with IFN-g + CD45RO 2 CD8 T cells (Supplemental Fig.…”
Section: C9-hi Cd8 T Cells Display a Predominantly Memory Phenotypesupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with these previous reports, we observed that memory (CD45RO + ) CD8 T cells from donors 3 and 4 that display the conventional unimodal pattern of SAP expression with the 1C9-SAP Ab clone also expressed higher levels of SAP in terms of median fluorescence intensity (MFI) (2.5-4 times greater than the [CD45RO 2 ] CD8 T cells) (Supplemental Fig. 2) (29). This trend was repeated when we gated on their IFNg-producing CD8 T cells as the IFN-g + CD45RO + CD8 T cells displayed a higher MFI for SAP compared with IFN-g + CD45RO 2 CD8 T cells (Supplemental Fig.…”
Section: C9-hi Cd8 T Cells Display a Predominantly Memory Phenotypesupporting
confidence: 91%
“…Analyses performed in SLE patients and controls have demonstrated that SAP expression levels are higher in effector/memory CD4 T cells compared with naive CD4 T cells, and a separate study demonstrated that memory T cells harbor a greater proportion of SAP + T cells compared with naive T cells (8,29). Additionally, an examination of cases of spontaneous somatic reversion of the SAP mutations in XLPD-Type 1 patients has shown that this reversion is restricted to the memory CD8 T cell and CD4 T cell subsets (14,16).…”
Section: C9-hi Cd8 T Cells Display a Predominantly Memory Phenotypementioning
confidence: 99%
“…Twenty‐five patients were diagnosed with FHL, nine with FHL type 2 (FHL2), 16 with FHL type 3 (FHL3) and 29 with EBV‐HLH. Flow cytometric and genetic analyses were performed in six out of nine male patients diagnosed with EBV‐HLH (analyses were performed by Dr. H. Kanegane at Tokyo Medical and Dental University), and X‐linked lymphoproliferative syndrome (XLP) was ruled out (Marsh et al , ; Zhao et al , ; Yang et al , ). The remaining three patients were not screened for XLP.…”
Section: Resultsmentioning
confidence: 99%
“…When XLP is suspected, flow cytometric analysis of SAP and XIAP can be performed. 464,465 SAP expression levels correlate well with genetic alterations in SH2D1A; normal XIAP expression despite XIAP mutations is more frequent. Therefore detection of normal protein expression does not exclude the diagnosis of XLP2.…”
Section: Diseases Of Immune Dysregulationmentioning
confidence: 92%